2021
DOI: 10.1021/acs.jpca.1c00900
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of an Embedded Five-Membered Ring in Polycyclic Aromatic Hydrocarbons via the Hydrogen-Abstraction–Acetylene-Addition Mechanism: A Theoretical Study

Abstract: Five-membered rings are constituents of many polycyclic aromatic hydrocarbons (PAHs), and their presence on the edges of large PAHs has been repeatedly observed experimentally. However, modern kinetic combustion models often do not consider the growth of PAHs through the transformation of the five-membered rings. In connection with the above, we carried out a theoretical study of the mechanism of hydrogen-abstraction−acetylene-addition (HACA) transformation of an embedded five-membered ring on the armchair PAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This is mainly due to the presence of the embedded five-membered ring structure, which reduces the stability of π electrons in the bay area and makes them more likely to be activated by losing H in the H-abstraction process. [41,67,68] Therefore, in a sense, the energy required for the activation of the HACA mechanism is reduced and the process of the mechanism is accelerated. This factor also exists in the process of acenaphthene forming acephenanthrylene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly due to the presence of the embedded five-membered ring structure, which reduces the stability of π electrons in the bay area and makes them more likely to be activated by losing H in the H-abstraction process. [41,67,68] Therefore, in a sense, the energy required for the activation of the HACA mechanism is reduced and the process of the mechanism is accelerated. This factor also exists in the process of acenaphthene forming acephenanthrylene.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from the flux diagram (Figure 8), it is easier for the HACA mechanism to form the six‐membered ring structures than the acetylene direct addition to forming the five‐membered ring structures. This is mainly due to the presence of the embedded five‐membered ring structure, which reduces the stability of π electrons in the bay area and makes them more likely to be activated by losing H in the H‐abstraction process [41,67,68] . Therefore, in a sense, the energy required for the activation of the HACA mechanism is reduced and the process of the mechanism is accelerated.…”
Section: Resultsmentioning
confidence: 99%
“…The MESS software package was utilized for the RRKM-ME calculations, where partition functions and densities of states for local mimima and numbers of states for transition states were computed within the Rigid-Rotor, Harmonic-Oscillator (RRHO) model. The Lennard-Jones parameters were estimated using the general expressions for ε and σ depending on the molecular mass proposed by Wang and Frenklach for PAH molecules, whereas the parameters for the bath gas (N 2 ) were taken from the papers by Vishnyakov et al , Our previous calculations showed that moderate changes in the Lennard-Jones parameters within the ranges corresponding to four- to six-ring PAHs result in insignificant changes of the calculated pressure-dependent rate constants of less than 10% . The collisional energy transfer parameters in RRKM-ME calculations were described within the “exponential down” model, where the temperature dependence of the parameter α for the deactivating wing of the energy transfer function was expressed as α­( T ) = α 300 ( T /300) n , where n = 0.85 and α 300 = 247 cm –1 are “universal” values proposed by Jasper and Miller for hydrocarbons …”
Section: Calculation Methodsmentioning
confidence: 99%
“…17,18 For uniformity, we kept the same α 300 = 424 cm −1 and n = 0.62 values for pyrenyl, but it is our experience that for the reactions involving PAH, differences in pressure-dependent rate constants using these values and with the “universal” values for hydrocarbons proposed by Jasper and Miller, 19 α 300 = 247 cm −1 and n = 0.85, do not exceed 10%. 20…”
Section: Methodsmentioning
confidence: 99%